Shakespeare's shrine : the Bard's birthplace and the invention of Stratford-upon-Avon - Thomas, Julia, 1971- (Haney Foundation series., 2012)
"Anyone who has paid the entry fee to visit Shakespeare's Birthplace on Henley Street in Stratford-upon-Avon - and there are some 700,000 a year who do so - might be forgiven for taking the authenticity of the building for granted. The house, as the official guidebooks state, was purchased by Shakespeare's father, John Shakespeare, in two stages in 1556 and 1575, and William was born and brought up there. The street itself might have changed through the centuries - it is now largely populated by gift and tea shops - but it is easy to imagine little Will playing in the garden of this ancient structure, sitting in the inglenook in the kitchen, or reaching up to turn the Gothic handles on the weathered doors. In Shakespeare's Shrine Julia Thomas reveals just how fully the Birthplace that we visit today is a creation of the nineteenth century. Two hundred years after Shakespeare's death, the run-down house on Henley Street was home to a butcher shop and a pub. Saved from the threat of an ignominious sale to P.T. Barnum, it was purchased for the English nation in 1847 and given the picturesque half-timbered façade first seen in a fanciful 1769 engraving of the building. A perfect confluence of nationalism, nostalgia, and the easy access afforded by rail travel turned the house in which the Bard first drew breath into a major tourist attraction, one artifact in a sea of Shakespeare handkerchiefs, eggcups, and door-knockers. It was clear to Victorians on pilgrimage to Stratford just who Shakespeare was, how he lived, and to whom he belonged, Thomas writes, and the answers were inseparable from Victorian notions of class, domesticity, and national identity. In Shakespeare's Shrine she has written a richly documented and witty account of how both the Bard and the Warwickshire market town of his birth were turned into enduring symbols of British heritage - and of just how closely contemporary visitors to Stratford are following in the footsteps of their Victorian predecessors."--Project Muse.